Implementasi E-Ticketing Dalam Transjabodetabek Untuk Mewujudkan Integrasi Trasnportasi di Jabodetabek - Dwinda Rizky Hadinugrah; Soewanto Adhi; Lusia Astrika (Journal of Politic and Government Studies, 2017)
Abstract Implementation of e-ticketing in Transjabodetabek as an answer of transportation problem in Jabodetabek. People who previously used private vehicles were expected to move to Transjabodetabek for mobilization to Jakarta from buffer city or vice versa because with the implementation of e-ticketing Transjabodetabek mobilization of everyday activities easier, faster, and safer.The research method used is qualitative approach with data collection technique; observation, interview and document study. The informants in this research are Bussines Development Analyst PT Transportasi Jakarta, Staff Directorate of Development Planning BPTJ Kemenhub, Executing Staff Field Activity Field Road Transportation Office of DKI Jakarta Province, and 3 (three) Transjabodetabek users.The results showed that in the implementation of e-ticketing Transjabodetabek found four supporting factors and two obstacles in implementation. The first supporting factor of communication is the purpose of apllied e-ticketing Transjabodetabek is suitable for transportation speed and security, but there is still a goal that has not been done, it is the integration between modal in Jabodetabek like with KRL and others. The second is the bureaucracy structure where the stakeholders involved already have a role but there is still overlap in terms of supervision of implementation. Third is the resources where everything is good both in terms of staff / human resources and facilities. The last is the disposition related characteristics of officers in providing services that are considered already fast but still found some officers who are not friendly. In terms of implementation barriers there are two obstacles, the first is information due to the lack of socialization, there are people who still do not know how to use and the usefulness of the e-ticket. Then the second is the division of potential where there is still overlap between stakeholders in the implementation of this Transjabodetabek e-ticketing.Recommendations can be done by the implementor is improving the quality of service by conducting various training so that the service is more friendly. Then there needs a clear division of tasks so there’s no more overlap and re-disseminated socialization and education about e-ticketing, especially to people who first use.Keywords: Implementation, Transportation, E-ticketing